Three year observations of water vapor and energy fluxes over agricultural crops in two regional climates of Southwest Germany - Hans-Dieter Wizemann; Joachim Ingwersen; Petra Högy; Kirsten Warrach-Sagi; Thilo Streck; Volker Wulfmeyer (Meteorologische Zeitschrift, 2015)
Reliable regional climate projections need improved land-surface-atmosphere models in which land-surface exchange, in particular the role of the vegetation, is well represented. To get a better understanding of the land-surface exchange and as a data basis for model development, parameterization and validation, long-term eddy-covariance measurements were performed over agricultural landscapes in two regions of Southwest Germany with different regional climate: near the northern Upper Rhine Valley with a mild climate and on the Swabian Jura, a low mountain range plateau where the climate is colder and wetter. At each study site we installed three eddy-covariance weather stations and monitored the soil water regime as well as the crop development. We describe the characteristics of the study sites, the experimental field work and data processing. The dynamics of water vapor and energy fluxes over winter wheat, winter oilseed rape and silage maize were evaluated for the time period from 2009 to 2011. The accuracy of the measured energy and matter fluxes limited by statistics and instrumental noise error was better than 10 %. Energy fluxes and albedo were closely linked to crop development. The albedo increased and decreased with LAI. Albedo values up to 0.28 were measured over flowering oilseed rape. The winter crops developed faster in the milder climate. The daily average of latent heat flux was about 10–20 Wm−2 higher and that of sensible heat flux about 5–15 Wm−2 lower there in comparison with the colder climate. Differences between both regions with regard to the turbulent fluxes are assigned to be mainly due to differences in vapor pressure deficit. Actual and prevailing weather conditions had a large impact on energy fluxes so that notable differences of flux dynamics were observed not only between the regions but also at one site for the same crop in different years. The observed long-term flux dynamics are discussed with respect to phenology, regional climate and the impact of prevailing weather conditions.